Implementación de un Sistema de Monitoreo de Caudal de Río San Pablo. - Chusin Lisintuña, William Rolando (2020)
This research consists in the implementation of a flow monitoring system in the San Pablo river. To carry out the same, the flow levels were initially mapped in different parts along the river at different times. With the above it was observed that overflows were really common, which became more intense in the months of the year corresponding to winter. In order to monitor these flow values, the sensors that are in charge of measuring this level and storing this information in a cloud destined for this purpose are installed in an area quite distant and rising up the river. Measurements of the speed and flow of the San Pablo River were made at an approximate distance of 5 km upwards in the course of the river. These measurements allowed an evaluation of the behavior of the river and an estimate of the travel time of a possible water strike. Two methodologies were followed to perform these measurements; The first consisted of the design of a device formed mainly by a flowmeter to obtain the water velocity values, and an arduino card that processes and visualizes said data. The second method is based on the use of a mobile application that gives an estimate of the speed of a natural water flow. For the positioning of the sensors in their respective locations, several parameters were taken into account, such as the availability of electricity and internet for the Gateway, and the range of the sensors by the Gateway. The data recovered by the sensors is stored in a space in the cloud that already has the necessary security policies to restrict access to them. In addition, it also has a WEB interface that allows you to visualize the current value of the flow rate at any time from the installation of these sensors.